2000
DOI: 10.1118/1.598960
|View full text |Cite
|
Sign up to set email alerts
|

Dose calculation and verification of intensity modulation generated by dynamic multileaf collimators

Abstract: While the development of inverse planning tools for optimizing dose distributions has come to a level of maturity, intensity modulation has not yet been widely implemented in clinical use because of problems related to its practical delivery and a lack of verification tools and quality assurance (QA) procedures. One of the prerequisites is a dose calculation algorithm that achieves good accuracy. The purpose of this work was twofold. A primary-scatter separation dose model has been extended to account for inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…The dosimetric accuracy of IMRT treatment planning systems for single fields has been reported to be better than 3% or 3 mm. 19 A study 20 using the MIMiC multileaf collimator, has shown that direct dose measurements at the isocenter agreed with the calculations within +3%. Recent studies have attempted to address the accuracy of calculated dose for the total plan transferred to a phantom compared with measurements for a series of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The dosimetric accuracy of IMRT treatment planning systems for single fields has been reported to be better than 3% or 3 mm. 19 A study 20 using the MIMiC multileaf collimator, has shown that direct dose measurements at the isocenter agreed with the calculations within +3%. Recent studies have attempted to address the accuracy of calculated dose for the total plan transferred to a phantom compared with measurements for a series of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The commissioning and quality assurance of IMRT and its associated treatment verification methods, have been the subject of numerous publications [55][56][57][58][59][60][61][62] . The main focus of the workshop was conventional MLC based IMRT, and the various delivery methods (segmental MLC and dynamic MLC).…”
Section: Qa and Deliverymentioning
confidence: 99%
“…Intensity modulated radiation therapy (IMRT),1 tomotherapy,2 image‐guided radiation therapy (IGRT),3, 4 volumetric‐modulated arc therapy (VMAT),5, 6 and small field treatments utilized in SRT and SBRT are examples of radiation delivery practice with more intricate work flow than “conventional” radiation therapy. Due to this increased complexity, new quality assessment (QA) strategies have been developed, including patient‐specific dose verification 7, 8, 9, 10. This patient‐specific QA measurement is only performed once for a treatment course that can include as many as 44 sessions.…”
Section: Introductionmentioning
confidence: 99%